Source of resistance in tomato (Lycopersicon esculentum) and inheritance of host resistance for tomato leaf curl disease - Hazra, P; Nath, S (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2000-05 to evaluate 25 tomato (Lycopersicon esculentum Mill.) genotypes for resistance to tomato leaf curl virus. The per cent disease incidence and co-efficient of infection in the genotypes was highest in early autumn (planting in last week of August), followed by spring-summer (planting in first week of February) and autumn-winter (planting in second week of October) seasons suggesting significant influence of environment on sympton expression apart from white fly population. The 3 moderately resistant lines emerged, viz. ’H 24’,’Agata’ and ’EC-321425’ showing very low coefficient of infection (2-6) were crossed with 5 highly susceptible testers with very high co-efficient of infection (above 21), namely ’Punjab Chhuhara’, ’Pusa Ruby’, ’Ratan’, ’Hisar Arun’ and ’Patharkutchi’ in line x tester mating design. The hybrids recorded a range of intermediate disease reaction and it varied widely in 2 seasons suggesting polygenic nature of disease resistance. In the early autumn season, overwhelming revelation of additive genetic component was recorded for tomato leaf curl virus resistance whereas in autumn-winter season, both additive and dominance gene effects was equally important seemingly manifesting complicated inheritance of resistance. Higher total phenol content in the leaves estimated at 80 days growth stage appeared to have determined the resistance actively in the host. Exploitable level of disease resistance could be achieved in very few hybrids involving moderately resistant x susceptible cross.